Radiation therapy patients’ interest in psychedelic-assisted therapy: results of a survey - Jino Park; Rufus Banks; Akul Munjal; Krishna Hanubal; Nicholas Peterson; Garrett Harada; Michael A. Hoyt; Erin H. Healy; Jeremy P. Harris (Radiation Oncology)
Abstract Background Comorbid mental health symptoms impact 30–40% of cancer patients, significantly compromising treatment adherence and increasing mortality rates. Among patients undergoing radiation therapy, which is delivered with palliative intent in nearly half of all cases and for those nearing end-of-life, these rates may be even higher. Emerging research underscores the promising potential of psychedelic-assisted therapy (PAT) in alleviating cancer-related psychological distress. However, the perspectives of cancer patients on the therapeutic utility of psychedelics remain unexplored. Methods and materials Adult patients with a cancer diagnosis were recruited in Radiation Oncology Clinic between May 2023 and August 2024. They included patients being evaluated before, during, or after radiation therapy. Data on demographics, medical history, prior psychedelic use, and measures of mental health burden and quality of life using validated questionnaires were collected to assess interest in PAT and factors associated with such interest. Results 100 patients enrolled in the study. 43% expressed interest in PAT, while 31% were opposed, and 26% were unsure. Prior diagnoses of mental health disorders like anxiety and depression, prior recreational psychedelic use, younger age, and male sex were positively associated with interest in PAT. Notably, patients with higher levels of depression, worse spiritual well-being, worse demoralization, worse quality of life, and more pain, symptoms that are targeted with PAT, were more likely to be receptive to it. Hesitancy was primarily attributed to a lack of information, cited by 43% of those not interested or unsure. Conclusion Psychedelic-assisted therapy represents a promising avenue to address critical gaps in cancer-related mental health care, and this study suggests that a substantial portion of cancer patients are receptive to and curious about this approach. The primary barrier to acceptance is informational, emphasizing the need for further research and education to dispel misconceptions and increase awareness of the safety and efficacy of psychedelic therapies. Future work should explore provider perspectives, patient outcomes, and the integration of PAT into palliative care frameworks.